Electrochemical and optical sensors made of composites of metal-organic frameworks and carbon-based materials. a review - M. Mokhtar, Nur Aina I.; M. Zawawi, Ruzniza; Wan M. Khairul; Yusof, Nor A. (Springer, 2022)
Rapid and selective sensing of biological substances and pollutants is developing rapidly in medicine and environmental sciences. Sensing performance depends on the material used as electrode modifier. Here, metal–organic frameworks are promising due to their high surface area and porosity, and their ability to adsorb guest molecules, yet they are limited by low conductivity and luminescence. The low conductivity issue can be solved by combining metal–organic framework with carbon-based materials of high conductivity and mechanical strength. Here, we review the synthesis and sensing applications of composites of metal–organic frameworks and carbon-based materials. We discuss charge transfer mechanisms and synergistic effects. Electrochemical and optical sensors allow to analyze metal ions, organic pollutants and biochemical molecules with a lowest detection limit of 0.12 nM.